Women’s Representation in Political Parties in Langsa City during the 2024 General Election: A Fiqh Siyasah Analysis - Anjas Affandi; M. Alkaf; Noviandy Noviandy (Al-Widad, 2026)
Women's political representation should ideally not only fulfill affirmative action quotas but also produce substantive representation in the policymaking process. However, in the 2024 local legislative election in Langsa City, women's representation in the Regional People's Representative Council (DPRK) remained below the 30% affirmative target and continued to face structural and cultural barriers. This study aims to analyze women's political representation based on Hanna Pitkin's four dimensions of political representation and to examine it from the perspective of fiqh siyasah. The research employs a qualitative case study approach using interviews, observations, and document analysis. The findings reveal that women have gained political access through the quota policy; however, descriptive and procedural representation have not been accompanied by optimal substantive representation due to patriarchal culture, weak party cadre development, limited resources, and insufficient political support. From the perspective of fiqh siyasah, women's political participation is consistent with the principles of al-'adl (justice), al-musawah (equality), asy-shura (consultation), and maslahah 'ammah (public interest), although their implementation remains suboptimal. This study contributes by demonstrating that the effectiveness of affirmative policies should be evaluated based on the quality of substantive representation rather than merely the fulfillment of administrative quotas.